2008
DOI: 10.1080/00207450601044686
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Dysgeusia and Dysesthesia in Stroke Patients

Abstract: This study investigated the relationship between dysgeusia and dysesthesia in stroke patients and evaluated the effect of carbamazepine therapy. Twenty-four patients with dysesthesia of the face, oral cavity, or tongue were divided into two groups: with and without subjective dysgeusia. Taste thresholds were objectively evaluated using the filter-paper taste test and electrogustometry. There was no significant difference in taste thresholds between the two groups. Carbamazepine had an effect on subjective dysg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
55
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(56 citation statements)
references
References 16 publications
0
55
0
1
Order By: Relevance
“…Impaired taste perception can result from lesions in several locations including the pons, insular cortices, and specific thalamic nuclei. 1–10 Several case reports have detailed altered taste as a result of isolated pontine lesions 26,10 as well as both isolated right and left insular lesions. 11,12 Deficits including ageusia (inability to taste), hypogeusia (decreased ability to taste), and dysgeusia (distorted ability to taste) have also been described.…”
mentioning
confidence: 99%
“…Impaired taste perception can result from lesions in several locations including the pons, insular cortices, and specific thalamic nuclei. 1–10 Several case reports have detailed altered taste as a result of isolated pontine lesions 26,10 as well as both isolated right and left insular lesions. 11,12 Deficits including ageusia (inability to taste), hypogeusia (decreased ability to taste), and dysgeusia (distorted ability to taste) have also been described.…”
mentioning
confidence: 99%
“…7 This theory is supported by numerous functional MRI studies demonstrating that the insular, parietal, frontal opercular, and orbitofrontal cortical areas are activated with gustatory pathway stimulation. 17,20 It is important to note that damage to the somatosensory pathways may also result in dysgeusia independent of central gustatory pathways, based on findings by Etoh et al, 10 who studied objective dysgeusia (as measured with electrogustometry and filter paper testing) in patients with lesions in the pons, thalamus, putamen, or insula.…”
Section: Interpretation Of Taste: Theories and Mechanismsmentioning
confidence: 99%
“…One small study found that carbamazepine improved stroke-induced dysgeusia. 10 Activation of cannabinoid receptors by delta-9-tetrahydrocannibinol has been shown to improve food palatability, thus increasing appetite and food intake, possibly through stimulation of dopamine production in the nucleus accumbens. [43][44][45][46] Future research in this area will be helpful in identifying potential therapies.…”
Section: Identifying and Addressing Taste Disordersmentioning
confidence: 99%
See 2 more Smart Citations